Удлинение интервала QT как предиктор внезапных кардиологических событий (данные скринингового исследования школьников) - Сенаторова, А.С.; Гончарь, М.А.; Санина, И.А.; Оникиенко, А.Л.; Чайченко, Т.В.; Страшок, А.И.; Цымбал, В.Н. (Таврический медико-биологический вестник, 2013)
Представлені результати скринінгу 731 школяра Харківського регіону. За даними ЕКГ у 32,65±1,95%
дітей встановлені порушення процесів реполяризації, у 11,51±1,32% – синдром ранньої реполяризації
шлуночків, у 3,4±0,76% – подовження коригованого інтервалу QTс більше 450мс; у 1,09±0,48% – синдром
укороченого інтервалу QT. 21,58±2,99% школярів займаються в спортивних секціях, з них – 18,87±3,2%
дітей на рівні аматорського спорту та 2,71±3,2% дітей – на рівні спорту високих досягнень. Встановлено
що, тільки 20,0±2,91% всіх обстежених школярів задовільно переносять фізичні навантаження. У 36,8±2,1%
дітей, що займаються спортом, виявлено суб’єктивні та об’єктивні зміни з боку серцево-судинної системи.
Тривалість коригованого інтервалу QTс не залежала від віку і склала Ме=398[Lq=380;Uq=414]мс. Частота
змін на ЕКГ спокою у школярів Харківського регіону склала 43,4%, після навантаження – 63,2%. The results of the screening of 731 pupils from Kharkiv region were presented. According to the ECG
examination, 32,65 ± 1,95% of children recorded violations of repolarization: from 11,51 ± 1,32% – early ventricular
repolarization syndrome, with 3,44 ± 0,76% – corrected QTc interval prolongation more than 450MS; from 1,09
± 0,48% – syndrome of the short QT interval. Duration of corrected QTc interval was independent of age and
was Me = 398 [Lq = 380; Uq = 414] ms. There was a trend towards a slight increase in QTc in children of 11 and
13 ages (Me: = 402 [Lq = 390; Uq = 413] ms and Me = 404 [Lq = 385; Uq = 419] ms, respectively). The maximum
acceptable QTc interval less than 455ms (95 percentile) were reported in 13 years old children. The lowest values
of the electrical systole of the heart were noticed at the age of 10 years and reached 330ms. Thus, the frequency
of changes on standard ECG in school children from Kharkiv region was 43.4%, after physical exercises – 63.2%. The
study showed the need of ECG examination as a screening test to identify early markers of cardiac disease in children,
and to identify pupils with low tolerance to physical exercises and the issue of admission to the physical education
and sports. The high frequency of changes in the electrical systole in pupils necessitates further cardiac examination
in a hospital in order to prevent sudden cardiovascular events in childhood.